Functional Brain Activity Changes after 4 Weeks Supplementation with a Multi-Vitamin/Mineral Combination: A Randomized, Double-Blind, Placebo-Controlled Trial Exploring Functional Magnetic Resonance Imaging and Steady-State Visual Evoked Potentials during Working Memory - White, David J.; Cox, Katherine H. M.; Hughes, Matthew E.; Pipingas, Andrew; Peters, Riccarda; Scholey, Andrew B. (Frontiers in Aging Neuroscience, 2016)
This study explored the neurocognitive effects of four weeks daily supplementation with a multivitamin and mineral combination (MVM) in healthy adults (aged 18-40 years). Using a randomized, double-blind, placebo-controlled design, participants underwent assessments of brain activity using functional Magnetic Resonance Imaging (fMRI; n=32, 16 females) and Steady-State Visual Evoked Potential recordings (SSVEP; n=39, 20 females) during working memory and continuous performance tasks at baseline and following four weeks of active MVM treatment or placebo. There were several treatment-related effects suggestive of changes in functional brain activity associated with MVM administration. SSVEP data showed latency reductions across centro-parietal regions during the encoding period of a spatial working memory task following four weeks of active MVM treatment. Complementary results were observed with the fMRI data, in which a subset of those completing fMRI assessment after SSVEP assessment (n=16) demonstrated increased BOLD response during completion of the Rapid Visual Information Processing task (RVIP) within regions of interest including bilateral parietal lobes. No treatment-related changes in fMRI data were observed in those who had not first undergone SSVEP assessment, suggesting these results may be most evident under conditions of fatigue. Performance on the working memory and continuous performance tasks did not significantly differ between treatment groups at follow-up. In addition, within the fatigued fMRI sample, increased RVIP BOLD response was correlated with the change in number of target detections as part of the RVIP task. This study provides preliminary evidence of changes in functional brain activity during working memory associated with four weeks of daily treatment with a multivitamin and mineral combination in healthy adults, using two distinct but complementary measures of functional brain activity.